Combination of Active Cycle of Breathing Techniques (ACBT) and Chest Physiotherapy on the Effectiveness of Airborne Cleaning in Pulmonary TB Patients - Risti Puji Listari; Eppy Setiyowati; Chilyatis Zahroh (Journal Of Nursing Practice, 2025)
Background: The occurrence of ineffective airway clearance in pulmonary TB patients begins with disease transmission which occurs when a patient with positive BTA sneezes or coughs without covering his nose or mouth so that germs will spread into the air in the form of phlegm or droplets. In the pathophysiology of pulmonary TB, it can cause destruction or fibrosis of the airways and damage the lung parenchyma, causing tracheal/pharyngeal edema, increased secretion production, sputum obstruction, rupture of blood vessels or even hemaptoea, resulting in the airway being ineffective and causing shortness of breath. Purpose: The aim of this research isexplain the study aims to determine the effect of a combination of Active Cycle of Breathing Techniques (ACBT) and chest physiotherapy on the effectiveness of airway clearance in pulmonary TB patients. Methods: The method used was quasi experimental with a pretest-posttest control group design approach. This design involved two groups, namely a combination intervention group of Active Cycle of Breathing Techniques (ACBT) and Chest Physiotherapy and a control group. Data collection was carried out using direct observation sheets and medical records. Results: Based on the test results using Mann Whitney, a p value of 0.000 was obtained, where the value was <0.05, which means there was a difference in the airway clearance score between the intervention and control groups in the delta/change data, where based on the mean value, the airway clearance score for the intervention group was obtained. the increase in score was greater than the control group when delta/change data. Conclusion: Combination of Active Cycle of Breathing Techniques (ACBT) and Chest Physiotherapy on the Effectiveness of Airway Clearing in Pulmonary TB Patients and is easy to do.